Re-evaluating the Roman West in the 3rd c. A.D. - Witschel, Christian (Journal of Roman archaeology, 2004)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1047759400008242/resource/name/firstPage-S1047759400008242a.jpg
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.09.2024